Characterization of a Species-Specific Insulinase-Like Protease in Cryptosporidium parvum - Zhang, Shijing; Wang, Yuping; Wu, Haizhen; Li, Na; Jiang, Jianlin; Guo, Yaqiong; Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2019)
Cryptosporidium parvum is an intracellular protozoan that can cause severe diarrhea in humans and various mammals. Results of a comparative genomic analysis indicated that genes encoding two C. parvum-specific insulinase-like proteases (INS19 and INS20), cgd6_5510 and cgd6_5520, are lost in many Cryptosporidium species. In this study, we provided evidence indicating that cgd6_5510 and cgd6_5520 are fragments of a full gene (cgd6_5520-5510) encoding one insulinase-like protease (INS20-19) that is similar in structure to classic insulinases. We expressed cgd6_5510 in Escherichia coli for antiserum preparation, and found the protein (INS19) was partially degraded. A ~180 kDa protein of INS20-19 was specifically recognized by the polyclonal anti-INS19 antiserum in sporozoite lysate. We observed that INS20-19 is likely a protein with high expression in the apical region of sporozoites, and neutralization of the protein led to a partial reduction of parasite load in HCT-8 and MDBK cell cultures at 24 h. Taken together, our findings support the involvement of INS20-19 in the invasion or early developmental process of C. parvum.